Fixed Assets Fair Value and Historical Value – Practical Problems with Implementation and Interpretation - Krzysztof Zawadzki (Contemporary Economics)
The article presents practical problems with implementation of fixed assets fair value during the acquisition processes. This has influence on the financial statements making and their research by accouters and auditors. In the article, the author would like to find the solution, how the fair value can be used on valuation of fixed assets and which method of it is better during the financial crisis period.